2019
DOI: 10.1111/eci.13164
|View full text |Cite
|
Sign up to set email alerts
|

Pythagorean self‐awareness intervention: A novel cognitive stress management technique for body weight control

Abstract: Background Over the past decades, the prevalence of obesity has markedly increased worldwide. Stress is recognized as a substantial contributor to increased body weight; therefore, stress management interventions, especially cognitive behavioural, are becoming increasingly popular. The impact of stress management on stress‐ and obesity‐related biomarkers (eg blood lipid profile, HBA1c, inflammatory biomarkers, such as CRP) has been scarcely studied. The aim of this study was to assess the effect of a novel cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
1
13
0
3
Order By: Relevance
“…Secondary outcomes i.e., sleep quality and self-efficacy were also improved after PSAI (Charalampopoulou et al, 2020). Encouraging results have been also reported by Simos et al who implemented the PSAI on obese/ overweight individuals and found significant effect sizes with respect to perceived stress levels, lifestyle and eating behaviours (Simos et al, 2019).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Secondary outcomes i.e., sleep quality and self-efficacy were also improved after PSAI (Charalampopoulou et al, 2020). Encouraging results have been also reported by Simos et al who implemented the PSAI on obese/ overweight individuals and found significant effect sizes with respect to perceived stress levels, lifestyle and eating behaviours (Simos et al, 2019).…”
Section: Discussionsupporting
confidence: 62%
“…Encouraging results have been also reported by Simos et al . who implemented the PSAI on obese/overweight individuals and found significant effect sizes with respect to perceived stress levels, lifestyle and eating behaviours ( Simos et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…А recently introduced cognitive-based stress management technique, the "Pythagorean Self-Awareness Intervention (PSAI)", seems to have promising effects on patients suffering from obesity, insomnia, multiple sclerosis, mild cognitive impairment or acne vulgaris. In a recent study of Simos et al [28], implementation of the PSAI for 8 weeks in adults with obesity, resulted in statistically significant decreases in perceived stress, serum and saliva cortisol concentrations, body mass index (BMI) and obesity-related biomarkers. Also, in the study of Darviri et al [29], patients with mild cognitive impairment who took part in PSAI, showed significant improvements in cognition, stress perception, anxiety, depression and self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of Simos et al. [ 28 ], implementation of the PSAI for 8 weeks in adults with obesity, resulted in statistically significant decreases in perceived stress, serum and saliva cortisol concentrations, body mass index (BMI) and obesity-related biomarkers. Also, in the study of Darviri et al.…”
Section: Introductionmentioning
confidence: 99%